Induction of adventitious shoot regeneration in chrysanthemum as affected by the season - Zalewska, Małgorzata; Lema-Rumińska, Justyna; Miler, Natalia; Gruszka, Magdalena; Dąbal, Weronika (In vitro cellular & developmental biology. Plant, 2011)
The subject of investigation was Chrysanthemum x grandiflorum (Ramat.) Kitam., 'Satinbleu'. Leaf explants and internodes were excised from the middle part of the donor sterile plant. Two methods of explant inoculation were applied: explants were placed polarly and horizontally. Modified MS medium (Murashige and Skoog 1962), supplemented with 11.4 μM indoleacetic acid and 2.7 μM 6-benzylaminopurine, were prepared to induce adventitious bud formation. Four dates of explant inoculation on the medium were tested: January 15, April 15, July 15, and October 15. Thus, regeneration occurred in winter, spring, summer, and autumn. In the present study, a more intensive regeneration in 'Satinbleu' chrysanthemum was observed in summer and autumn than in spring and winter, irrespective of the kind of explant and the inoculation method.